Improving Writing Skills of Non-Native English Undergraduates through Artificial Intelligence Tools: An Experimental Study - Alhawamdeh, Basem; Ajmal, Muhammad; Sultana, Fatema; Andleeb, Nazish; Ahmed Mohamed, Areig Osman (Journal of Education Culture and Society, 2026)
Aim. The research focuses on the impact of Artificial Intelligence (AI) tools on the writing abilities of undergraduate students who are non-native speakers of English. The provision of teaching guidance and AI literacy are vital to the constructive, responsible, and ethical integration of AI tools in teaching the English language. Methods. During a four-week period, Grammarly and ChatGPT were used as integrated instructional tools which incorporated a mixed-methods approach under a quasi-experimental framework. Twenty (20) students’ part of the Department of English Language and Literature completed the pre and post writing intervention tasks that were analysed with a rubric which evaluated the writing for grammar, vocabulary, coherence and academic tone. Results. The analysed data comprised descriptive statistics and paired-sample t-tests which also calculated the respective effect size as Cohen’s dz. The findings indicated a statistically significant improvement across all writing tasks (p < .001) and the effect size measures suggest the improvement was large and substantive (dz = 1.45–2.04). The mean scores of the grammar and coherence constructs were the highest across the tasks, indicating that there was a positive change in AI feedback focused on instructional coherence and organization. Conclusions. Both the focus group and the open-ended questionnaires which were analysed qualitatively generated data with explanatory power that was in parallel with the students’ confidence, autonomy and awareness of errors was amplified. Although, over-dependence on the AI tools, feedback disconnects, and at times, wrong contextualisation had some reported gaps. The results imply that, with teacher mediation, AI tools can act as compatible additions to improving writing proficiency.